Sex‐Specific Associations of Oral Anticoagulant Use and Cardiovascular Outcomes in Patients With Atrial Fibrillation. Issue 8 (18th August 2017) - Palamaner Subash Shantha, Ghanshyam; Mentias, Amgad; Inampudi, Chakradhari; Kumar, Anita A.; Chaikriangkrai, Kongkiat; Bhise, Viraj; Deshmukh, Abhishek; Patel, Nileshkumar; Pancholy, Samir; Horwitz, Phillip A.; Mickelsen, Steven; Bhave, Prashant D.; et al.
Abstract : Background: Sex‐specific effectiveness of rivaroxaban (RIVA), dabigatran (DABI), and warfarin in reducing myocardial infarction (MI), heart failure (HF), and all‐cause mortality among patients with atrial fibrillation are not known. We assessed sex‐specific associations of RIVA, DABI, or warfarin use with the risk of MI, HF, and all‐cause mortality among patients with atrial fibrillation. Methods and Results: Medicare beneficiaries (men: 65 734 [44.8%], women: 81 135 [55.2%]) with atrial fibrillation who initiated oral anticoagulants formed the study cohort. Inpatient admissions for MI, HF, and all‐cause mortality were compared between the 3 drugs separately for men and women using 3‐way propensity‐matched samples. In men, RIVA use was associated with a reduced risk of MI admissions compared with warfarin use (hazard ratio [95% confidence interval (CI): 0.59 [0.38–0.91]), with a trend towards reduced risk compared with DABI use (0.67 [0.44–1.01]). In women, there were no significant differences in the risk of MI admissions across all 3 anticoagulants. In both sexes, RIVA use and DABI use were associated with reduced risk of HF admissions (men: RIVA; 0.75 [0.63–0.89], DABI; 0.81 [0.69–0.96]) (women: RIVA; 0.64 [0.56–0.74], DABI; 0.73 [0.63–0.83]) and all‐cause mortality (men: RIVA; 0.66 [0.53–0.81], DABI; 0.75 [0.61–0.93]) (women: RIVA; 0.76 [0.63–0.91], DABI; 0.77 [0.64–0.93]) compared with warfarin use. Conclusions: RIVA use and DABI use when compared with warfarin use was associated with a reduced risk of HF admissions and all‐cause mortality in both sexes. However, reduced risk of MI admissions noted with RIVA use appears to be limited to men.